Genome Sequence of Staphylococcus arlettae Strain CVD059, Isolated from the Blood of a Cardiovascular Disease Patient - Dinakaran, Vasudevan (American Society for Microbiology, 2012)
We have isolated a Staphylococcus arlettae strain, strain CVD059, from the blood of a rheumatic mitral stenosis patient. Here, we report the genome sequence and potential virulence factors of this clinical isolate. The draft genome of S. arlettae CVD059 is 2,565,675 bp long with a G+C content of 33.5%.